Improving efficiency and effectiveness of budget, labor, and inventory allocation decision making through decision support system - Wahyudi, Agung; Setyawan, Bayu; Sapuguh, Iman; Ahlina, Nur; Rosalinda, Adinda Sandra (Jurnal Teknik Informatika C.I.T Medicom, 2024)
This research aims to improve the efficiency and effectiveness of budget, labor, and inventory allocation decision making at PT Telkom through the application of the TOPSIS method. Using a decision matrix that includes five alternatives and three criteria, this analysis ranks each alternative based on proximity to the positive ideal solution and distance to the negative ideal solution. The results show that Alternative D is the best choice, signifying superiority in the combination of measured values. These recommendations provide strategic guidance for PT Telkom in optimizing resource management, but keep in mind that the results are relative and need periodic evaluation to maintain relevance in the context of dynamic changes. This research contributes to the decision-making and resource management literature by applying systematic methods to complex business situations.